An intelligent anti-phishing solution: password-transaction secure window. (18th July 2011) - Choukse, Dharmendra; Singh, Umesh Kumar; Kanellopoulos, Dimitris
Current phishing attacks cause serious problems to both organisations and users. Phishing attackers try to steal the confidential information of the users such as their username, password etc. Phishing is done either by e-mails or instant messaging or by a spoofed website which is an exact replica of original one. It is very difficult to distinguish fake websites and legitimate websites. Homograph attacks help in phishing and make it more difficult for users to identify them. Some malware like key-loggers also help to steal the crucial information. A different type of malware called transaction generator (TG)is also used by attackers. Instead of passing the confidential information to attackers, a TG waits until users login into their accounts and then does the transaction illegally in the background. In this paper, we present several anti-phishing methods with their pros and cons. In addition, we propose an intelligent anti-phishing solution named Password-Transaction Secure Window (PTSW) in order to secure users and their personal information. The PTSW is a cheap and efficient solution against password and transaction attacks.